2015
DOI: 10.1080/15384101.2015.1054086
|View full text |Cite
|
Sign up to set email alerts
|

ONC201 induces cell death in pediatric non-Hodgkin's lymphoma cells

Abstract: Abbreviations: TRAIL, TNF-related apoptosis-inducing ligand; DR5, death receptor 5; TNF, tumor necrosis family; NHL, non-Hodgkin's lymphoma.ONC201/TIC10 is a small molecule initially discovered by its ability to coordinately induce and activate the TRAIL pathway selectively in tumor cells and has recently entered clinical trials in adult advanced cancers. The anti-tumor activity of ONC201 has previously been demonstrated in several preclinical models of cancer, including refractory solid tumors and a transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…In accordance with ONC201-mediated activation of the ISR that B cells are highly sensitive to, lymphoma and myeloma were identified as the most ONC201-sensitive tumor types in a >1000 cell line screen [1]. ONC201 in vitro efficacy was confirmed in pediatric NHL cell lines that involved TRAIL-and caspase-dependent cell death [20]. ONC201 has demonstrated in vivo efficacy with prolongation of survival in an Em-myc transgenic B-cell lymphoma model [2].…”
Section: Discussionmentioning
confidence: 81%
“…In accordance with ONC201-mediated activation of the ISR that B cells are highly sensitive to, lymphoma and myeloma were identified as the most ONC201-sensitive tumor types in a >1000 cell line screen [1]. ONC201 in vitro efficacy was confirmed in pediatric NHL cell lines that involved TRAIL-and caspase-dependent cell death [20]. ONC201 has demonstrated in vivo efficacy with prolongation of survival in an Em-myc transgenic B-cell lymphoma model [2].…”
Section: Discussionmentioning
confidence: 81%
“…The anti-tumor activity of ONC201 has been demon strated in seve ral preclinical models of cancer, including refractory solid tumors, a transgenic lymphoma mouse mode land pediatric non-Hodgkin's lymphoma (NHL) cell lines. ONC201 caused a dosedependent reduction in the cell viability of NHL cell lines that resulted from induction of apoptosis [27]. An induction of TRAIL and its receptor TRAILR2/ DR5 was also observed in these cell lines.…”
Section: Fig 1 Schematic Representation Of the Role Of Tumor Necrosmentioning
confidence: 86%
“…It has been shown that Xenografting TNFRSF10B silenced pancreatic cancer cells in SCID-mice indicated that there was notable suppression of tumor growth [26]. Recently, it was shown that the TRAIL pathway is selectively activated by small molecule ONC201/TIC10 in tumor cells [27]. The anti-tumor activity of ONC201 has been demon strated in seve ral preclinical models of cancer, including refractory solid tumors, a transgenic lymphoma mouse mode land pediatric non-Hodgkin's lymphoma (NHL) cell lines.…”
Section: Fig 1 Schematic Representation Of the Role Of Tumor Necrosmentioning
confidence: 99%
“…provided proof for the anti-neoplastic activity of TIC10/ONC201 in different cancer entities including data showing enhanced therapeutic efficacy in an orthotopic glioblastoma model in vivo . More studies followed to confirm and extend the initial findings providing further proof for the anti-cancer activity of TIC10/ONC201 in colorectal cancer stem cell, pancreatic cancer or non-Hodgkin’s lymphoma models (35). In a multi-targeting approach, our own group was able to show that TIC10/ONC201 synergizes with ABT263, an inhibitor of anti-apoptotic Bcl-2 family proteins Bcl-2 and Bcl-xL, against glioblastoma and that the combination therapy causes tumor regression in vivo (6).…”
mentioning
confidence: 82%